PEMBERDAYAAN PEER GROUP SUPPORT UNTUK MENINGKATKAN KEMANDIRIAN PASIEN DIABETES MELLITUS DALAM MELAKUKAN SELF CARE MANAGEMENT DI WILAYAH KERJA PUSKESMAS DUNGINGI - Falah, Fakhriatul; Pratama, Eka Firmansyah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Gorontalo placed on 7th province with the highest diabetes mellitus sufferers from in Indonesia. One of the areas in the city of Gorontalo that has quite a high number of Diabetes Mellitus sufferers is the Dungingi sub-district with a total of 62 people over the last 3 months. 70% of DM sufferers who come to the Community Health Center for examination have uncontrolled blood sugar because the patient does not carry out proper self care rules, whether in diet, physical activity, stress management and controlling blood sugar. Therefore, this community service activity is expected to be able to increase the knowledge, skills and abilities of diabetes mellitus patients in carrying out self-care so that the quality of life of Diabetes Mellitus sufferers in the Dungingi Region can improve. This community service programme aims to empower peer group support of diabetes patient to increase the motivation of DM patients to carry out self-care management. Apart from involving patients, health cadres are also trained as peer group facilitators so that the sustainability of this activity in the community can be guaranteed. This Community Service begins with socialization and formation of peer groups, peer group activity sessions, and evaluation. From the results of this activity, it was found that there was improvement in self-care abilities in patients with an average increase of 8 scores with a pretest score of 18 and a posttest score of 27.8. It was also found that there was a decrease in blood glucose levels with average pretest value 295 mg/dL and posttest value 210 mg/dL